In vitro study of the preventive activity of fluoride varnish by X-ray diffraction - Dobrinka Mitkova Damyanova; Siyana Georgieva Atanasova (Intelektual Pustaka Media Utama, 2023)
In exogenous prophylaxis, fluoride is applied directly to the tooth surface through various gels, varnishes, foams, and toothpaste. According to the global burden of disease study conducted in 2017, more than 530 million children worldwide suffer from dental caries in their primary dentition. There are few developments in the selection of non-invasive methods in the application of mineralizing varnishes. The researchers investigated experimentally, in-vitro the preventive activity of the fluoride varnish Clinpro™ White Varnish with TCP 3M (CV), using a modern method of X-ray diffraction. The 20 temporary teeth were extracted due to physiological changes. Place of study was UMDC - city of Varna and Institute of Physical Chemistry